Cardiac Involvement in Women With Pathogenic Dystrophin Gene Variants - Solheim, Tuva Å.; Fornander, Freja; Raja, Anna A.; Møgelvang, Rasmus; Poulsen, Nanna S.; Dunø, Morten; Bundgaard, Henning; Vissing, John (Frontiers in Neurology, 2021)
Objective: To determine the frequency and extent of cardiac involvement in female carriers of pathogenic variants in DMD, 53 women were examined through an observational, cross-sectional study. Methods: Genetically verified female carriers of pathogenic DMD variants were examined by cardiac magnetic resonance imaging (CMR) with late gadolinium enhancement, echocardiography, 24-h Holter monitoring, ECG, and blood concentrations of skeletal and cardiac muscle biomarkers. Results: Fifty-three female carriers of pathogenic DMD variants (mean age 49.6 years, 33 associated with DMD, and 20 with BMD) were included in the study. Sixty-two percent had cardiac dysfunction on echocardiography. On CMR, 49% had myocardial fibrosis, 35% had dilated left ventricles, and 10% had left ventricular hypertrophy. ECGs were abnormal in 72%, and abnormal Holter monitoring was found in 43%. Age did not correlate with myocardial fibrosis or cardiac dysfunction. Myocardial fibrosis was more frequent in carriers of pathogenic variants associated with DMD vs. BMD (61 vs. 28%, p = 0.02). Conclusion: This study shows that cardiac involvement, affecting both structure and function of the heart, is found in over 2/3 of women with a pathogenic DMD variant. The study supports early cardiac screening, including ECG, Holter, and cardiac imaging, in this group of carriers, so that symptoms related to pathogenic variants in DMD can be recognized, and relevant treatment can be initiated. Longitudinal studies are needed to assess morbidity and mortality related to single, pathogenic DMD variants in women.